A single-visit field test of critical speed - Galbraith, A.; Hopker, J.; Lelliott, S.; Diddams, L.; Passfield, L. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To compare critical speed (CS) measured from a single-visit field test of the distance-time relationship with the "traditional" treadmill time-to-exhaustion multivisit protocol. Methods: Ten male distance runners completed treadmill and field tests to calculate CS and the maximum distance performed above CS (D'). The field test involved 3 runs on a single visit to an outdoor athletics track over 3600, 2400, and 1200 m. Two field-test protocols were evaluated using either a 30-min recovery or a 60-min recovery between runs. The treadmill test involved runs to exhaustion at 100%, 105%, and 110% of velocity at VO2max, with 24 h recovery between runs. Results: There was no difference in CS measured with the treadmill and 30-min- and 60-minrecovery field tests (P < .05). CS from the treadmill test was highly correlated with CS from the 30- and 60-min-recovery field tests (r = .89, r = .82; P < .05). However there was a difference and no correlation in D' between the treadmill test and the 30 and 60-min-recovery field tests (r = .13; r = .33, P > .05). A typical error of the estimate of 0.14 m/s (95% confidence limits 0.09-0.26 m/s) was seen for CS and 88 m (95% confidence limits 60-169 m) for D'. A coefficient of variation of 0.4% (95% confidence limits: 0.3-0.8%) was found for repeat tests of CS and 13% (95% confidence limits 10-27%) for D'. Conclusion: The single-visit method provides a useful alternative for assessing CS in the field.